Lithium-containing composite precursor, preparation method thereof, positive electrode material and battery
Patent Information
- Application Number
- CN202510850757.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-24
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2045-06-24
AI Technical Summary
然而,工业化生产的前驱体多采用共沉淀法制备,粉体粒度通常大于3μm,而锂盐颗粒尺寸为100~200μm,原料混合尺度受限于微米级别,需较高烧结温度和较长烧结时间,进而引发严重的锂镍混排现象,降低材料电化学性能,制约了其在动力电池中的大规模应用
相较于现有技术,本发明采用低成本的金属氧化物(喷雾热解法)、金属氢氧化物(共沉淀法)、锂盐及添加剂,通过纳米化处理并结合喷雾热处理,制备出含锂复合前驱体。该前驱体具有以下优势:
Smart Images

Figure CN120757161B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery technology, specifically to a lithium-containing composite precursor and its preparation method, a cathode material, and a battery. Background Technology
[0002] Ternary cathode material (LiNi) x Co y Mn 1−x−y O2 (oxygen dioxide) possesses high specific capacity and is currently the mainstream cathode material in the electric passenger vehicle field, widely used in pure electric vehicles with high range requirements. Currently, battery manufacturers mostly use polycrystalline materials, but these are prone to secondary particle breakage during cycling, leading to rapid capacity decay and affecting the overall vehicle lifespan. In contrast, monocrystalline materials can effectively suppress particle breakage, offering superior safety, cycle performance, and high compaction density. This meets the demands of new energy vehicles for long battery life and high energy density, making it an important future research direction for ternary materials.
[0003] The preparation of single-crystal ternary cathode materials is typically achieved through high-temperature solid-state calcination following a homogeneous mixing of lithium salt and precursor powder, a relatively simple process. However, industrially produced precursors are mostly prepared using a co-precipitation method, resulting in powder particle sizes typically greater than 3 μm, while lithium salt particles range from 100 to 200 μm. The raw material mixing scale is limited to the micrometer level, requiring higher sintering temperatures and longer sintering times, leading to severe lithium-nickel mixing and reduced electrochemical performance, thus hindering their large-scale application in power batteries. Although reducing the precursor powder particle size (e.g., nano-sizing) can improve sintering activity and electrochemical performance, the preparation of small-particle precursors is difficult, and problems such as low sintering yield, insufficient production capacity, and high costs exist, making it difficult to meet the rapidly growing demand for power batteries in the new energy vehicle market.
[0004] Nickel-cobalt-manganese oxides can be prepared by spray pyrolysis of a mixed solution of nickel, cobalt, and manganese chlorides or nitrates. Although this method can reduce the use of precipitants and wastewater treatment costs, its reactivity with lithium is low. It still requires high-temperature and long-term sintering and must be crushed to about 1μm before it can be used. It also faces the problems of low potting capacity, limited production capacity, and high cost, which is not conducive to cost reduction and efficiency improvement of power batteries for new energy vehicles.
[0005] In summary, the key to technological breakthroughs in the field is to significantly reduce the production cost of precursors while improving their sintering activity, increasing the amount of calcined material, and optimizing the overall cost. This is of great significance for promoting the upgrading of power battery technology for new energy vehicles and the sustainable development of the industry. Summary of the Invention
[0006] The purpose of this invention is to provide a lithium-containing composite precursor, its preparation method, a cathode material, and a battery.
[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A lithium-containing composite precursor is a secondary particle formed by the stacking of primary particles. It is composed of metal oxide, metal hydroxide, lithium salt and additives, with a particle size D50 of 5~50μm. The primary particles are nanoscaled with a size of less than 500nm.
[0008] A further technical solution is that the chemical formula of the metal oxide is (Ni x1 Co y1 Mn z1 Al t1 ) a1 M1 b1 O c1 Where 0 < x1 < 1, 0 < y1 < 1, 0 ≤ z1 < 1, 0 ≤ t1 < 0.1, x1 + y1 + z1 + t1 = 1, 0.9 < a1 ≤ 1, 0 ≤ b1 < 0.1, a1 + b1 = 1, c1 satisfies chemical valence balance, and M1 is one or more of the elements calcium, magnesium, aluminum, titanium, zirconium, tungsten, yttrium, strontium, niobium, molybdenum, vanadium, tantalum, boron, or phosphorus. The chemical formula of the metal hydroxide is (Ni x2 Co y2 Mn z2 Al t2 ) a2 M2 b2 (OH) c2 , 0 < x2 < 1, 0 < y2 < 1, 0 ≤ z2 < 1, 0 ≤ t2 < 0.1, x2 + y2 + z2 + t2 = 1, 0.9 < a2 ≤ 1, 0 ≤ b2 < 0.1, a2 + b2 = 1, c2 satisfies chemical valence balance, M2 is one or more of the elements calcium, magnesium, aluminum, titanium, zirconium, tungsten, yttrium, strontium, niobium, molybdenum, vanadium, tantalum, boron or phosphorus; The lithium salt is one or more of lithium carbonate, lithium bicarbonate, lithium hydroxide, lithium oxide, lithium acetate, lithium nitrate, and lithium oxalate. The additive is one or more of the carbonates, oxides, and hydroxides of element M3, where M3 is one or more of the elements calcium, magnesium, aluminum, titanium, zirconium, tungsten, yttrium, strontium, niobium, molybdenum, vanadium, tantalum, boron, or phosphorus.
[0009] In a further technical solution, the mass ratio of the metal oxide to the total mass of the metal oxide and metal hydroxide is 0~1:1, the molar ratio of lithium to metal is 0.70~1.50:1, and the mass ratio of the additive to the total mass of the metal oxide and metal hydroxide is 0~0.1:1.
[0010] Furthermore, the present invention also includes a method for preparing a lithium-containing composite precursor, comprising: S1, Preparation of metal oxides A first metal liquid with a metal concentration of 0.5~5.0 mol / L is obtained by dissolving and mixing the first nickel salt, the first cobalt salt, the first manganese salt and / or the first aluminum salt, and the M1 salt. The first molten metal was spray-pyrolyzed to obtain metal oxides; S2, Preparation of metal hydroxides A second metal solution with a metal concentration of 1.0~2.5 mol / L is obtained by dissolving a mixture comprising a second nickel salt, a second cobalt salt, a second manganese salt, and / or a second aluminum salt. Dissolve M2 salt to obtain M2 salt solution; Pure water, complexing agent, and precipitant are added to the reaction vessel as the reaction base liquid; The second metal solution, complexing agent, precipitant, and M2 salt solution are continuously added to the reactor simultaneously to maintain the temperature, complexing agent concentration, and solution pH in the reactor for co-precipitation reaction. After the reaction stops, the product is filtered, washed, and dried to obtain metal hydroxide; S3. After crushing the metal oxide and the metal hydroxide, add them to pure water along with lithium salt and additives and grind them into nanoparticles with D50 < 1 μm. Then, perform spray heat treatment to obtain the lithium-containing composite precursor.
[0011] In a further technical solution, in S1, the first nickel salt is one or a combination of nickel nitrate, nickel chloride, and nickel acetate; The first cobalt salt is one or a combination of cobalt nitrate, cobalt chloride, and cobalt acetate; The first manganese salt is one or a combination of manganese nitrate, manganese chloride, and manganese acetate; The first aluminum salt is one or a combination of aluminum nitrate, aluminum chloride, and aluminum acetate; The M1 salt is one or more of the following: calcium salt, magnesium salt, titanium salt, zirconium salt, tungsten salt, yttrium salt, strontium salt, niobium salt, molybdenum salt, vanadium salt, tantalum salt, borate, or phosphate.
[0012] In a further technical solution, in S2, the second nickel salt is one or a combination of nickel sulfate, nickel chloride, nickel nitrate, and nickel acetate; The second cobalt salt is one or a combination of cobalt sulfate, cobalt chloride, cobalt nitrate, and cobalt acetate; The second manganese salt is one or a combination of manganese sulfate, manganese chloride, manganese nitrate, and manganese acetate; The second aluminum salt is one or a combination of aluminum sulfate, aluminum chloride, aluminum nitrate, and aluminum acetate; The M2 salt is one or more of the following: calcium salt, magnesium salt, aluminum salt, titanium salt, zirconium salt, borate, tungsten salt, yttrium salt, strontium salt, niobium salt, molybdenum salt, vanadium salt, tantalum salt, borate, or phosphate. The complexing agent is one or more of the following: ammonia, ammonium sulfate, ammonium chloride, ammonium carbonate, ammonium bicarbonate, ammonium nitrate, and ammonium acetate. The precipitant is one or more of sodium hydroxide and potassium hydroxide, or a combination thereof.
[0013] In a further technical solution, in S1, the atomization method of the spray pyrolysis is one of pressure spray, centrifugal spray, or ultrasonic spray, the droplet size is less than 100μm, and the pyrolysis temperature is 600~1200℃; In S2, the reaction temperature is 40~75℃, the complexing agent concentration is 0.2~0.5mol / L, and the pH range is 10.60~12.60; In S3, the atomization method of the spray pyrolysis is one of pressure spray, centrifugal spray, or ultrasonic spray, the droplet size is less than 100μm, and the heat treatment temperature is 150~900℃.
[0014] Furthermore, this invention also discloses a lithium-ion battery cathode material, which is obtained by mixing a lithium-containing composite precursor with a lithium source, calcining the mixture at high temperature in an oxygen atmosphere, and then crushing it to obtain a single-crystal lithium-ion cathode material with the chemical formula Li(Ni). x Co y Mn z Al t ) a M b O c Where 0 < x < 1, 0 < y < 1, 0 ≤ z < 1, 0 ≤ t < 0.1, x + y + z + t = 1, 0.9 < a ≤ 1, 0 ≤ b < 0.1, a + b = 1, c satisfies chemical valence balance, M is one or more of the elements calcium, magnesium, aluminum, titanium, zirconium, tungsten, yttrium, strontium, niobium, molybdenum, vanadium, tantalum, boron or phosphorus, and the particle size D50 of the cathode material is 3~5 μm.
[0015] In a further technical solution, the lithium source is one or a combination of lithium carbonate, lithium bicarbonate, and lithium hydroxide; the calcination temperature is 650℃~1100℃, the oxygen concentration of the oxygen-containing atmosphere is 60%~100%, and the calcination time is 8~16h.
[0016] Furthermore, the present invention also discloses a lithium-ion battery, including a positive electrode sheet, wherein the positive electrode sheet is made of the aforementioned lithium-ion battery positive electrode material.
[0017] The terms “include,” “including,” and “have” used in this article are all open-ended, meaning they include but are not limited to.
[0018] Unless otherwise specified, the terms used herein generally have their ordinary meaning in the context of the art, the subject matter, and the specific context. Certain terms used to describe this case will be discussed below or elsewhere in this specification to provide additional guidance to those skilled in the art in describing the case.
[0019] The working principle and advantages of this invention are as follows: Compared to existing technologies, this invention utilizes low-cost metal oxides (spray pyrolysis), metal hydroxides (co-precipitation), lithium salts, and additives, and prepares a lithium-containing composite precursor through nano-sizing combined with spray pyrolysis. This precursor offers the following advantages: 1. High sintering activity: Nanoscale metal oxides and metal hydroxides have excellent sintering reactivity, and the nanoscale metal particles are in close contact with lithium salts, which significantly shortens the diffusion distance of lithium.
[0020] 2. Low-temperature sintering: Additives can melt at low temperatures to form a liquid phase environment, which promotes lithium diffusion and thus reduces the sintering temperature.
[0021] 3. Structural guidance effect: Metal hydroxides have a similar layered structure to the target cathode material and can act as crystal nuclei to induce the formation of layered single-crystal cathode materials, ultimately obtaining single-crystal materials with excellent electrical properties.
[0022] 4. Process economy: The lithium-containing composite precursor has a larger particle size and a higher calcination loading, which effectively reduces the sintering cost. Attached Figure Description
[0023] Appendix Figure 1 This is an electron microscope image of the lithium-containing composite precursor obtained in Example 1 of the present invention; Appendix Figure 2 This is an electron microscope image of the single-crystal cathode material prepared in Example 1 of the present invention; Appendix Figure 3 This is an electron microscope image of the metal hydroxide prepared in Comparative Example 1 of the present invention; Appendix Figure 4 This is an electron microscope image of the metal oxide prepared in Comparative Example 2 of the present invention. Detailed Implementation
[0024] The present invention will be further described below with reference to the accompanying drawings and embodiments: The present invention will be clearly described below with illustrations and detailed description. Any person skilled in the art who understands the embodiments of the present invention can make changes and modifications based on the technology taught in the present invention without departing from the spirit and scope of the present invention.
[0025] The terminology used herein is for the purpose of describing specific embodiments only and is not intended to limit the scope of this work. Singular forms such as “a,” “this,” “this,” “the,” and “the” as used herein also include plural forms.
[0026] Example 1: Includes the following steps: S1, Preparation of metal oxides a. Prepare a 2.0 mol / L first metal solution by mixing nickel chloride, cobalt chloride, manganese chloride, and magnesium chloride, wherein the molar ratio of nickel, cobalt, and manganese is 65:15:20, and the molar ratio of total nickel, cobalt, and manganese to magnesium is 99:1. M1 salt is magnesium chloride.
[0027] b. The first molten metal is subjected to centrifugal spray pyrolysis, with droplet size of 50 μm and pyrolysis temperature of 800℃, to obtain a metal oxide with a particle size D50 = 10.0 μm and chemical formula (Ni). 0.65 Co 0.15 Mn 0.20 ) 0.99 Mg 0.01 O 2.4 The particle size is 200~300nm; S2, Preparation of metal hydroxides a. Prepare a 2.0 mol / L second metal solution by mixing nickel chloride, cobalt chloride, and manganese chloride in a molar ratio of nickel, cobalt, and manganese of 65:15:20; dissolve magnesium chloride to obtain a 1.0 mol / L salt solution; b. Add pure water, ammonia water and 32% NaOH to the reaction vessel as the reaction base liquid; c. A co-precipitation reaction is carried out with the second metal liquid, magnesium chloride solution, ammonia water, and 32% NaOH at a temperature of 50℃ and a pH of 11.5. The M2 salt solution is a magnesium chloride solution.
[0028] d. After the reaction stops, the product is filtered, washed, and dried to obtain a metal hydroxide with the chemical formula (Ni). 0.65 Co 0.15 Mn 0.20 ) 0.99 Mg 0.01 (OH)2, particle size D50 = 3.8 μm; S3. The metal oxide and metal hydroxide are crushed to a particle size of 1.0 μm. They are then ground in pure water with lithium salt (lithium carbonate) and additive (boric acid). The mass ratio of the metal oxide to the total mass of the metal oxide and metal hydroxide is 0.8:1, the molar ratio of lithium to metal is 1.06, and the mass ratio of the additive to the total mass of the metal oxide and metal hydroxide is 0.005:1. After grinding into nanoparticles with D50 = 0.5 μm, they are subjected to spray heat treatment with a droplet size of 60 μm and a heat treatment temperature of 200℃ to obtain a lithium-containing composite precursor, wherein Li:(Ni+Co+Mn) = 0.90 and particle size D50 = 10.4 μm. S4. The lithium-containing composite precursor was mixed with lithium carbonate at a ratio of Li:(Ni+Co+Mn)=1.06 and sintered at 900℃ in an oxygen atmosphere for 11 hours. The mixture was then crushed to obtain a single-crystal lithium-ion battery cathode material. The chemical equation is Li(Ni) 0.65 Co 0.15 Mn 0.20 ) 0.99 Mg 0.01 O2, particle size D50=4.2μm.
[0029] Example 2: Includes the following steps: S1, Preparation of metal oxides a. Prepare a 2.0 mol / L first metal solution by mixing nickel chloride, cobalt chloride, and manganese chloride in a molar ratio of nickel, cobalt, and manganese of 65:15:20. b. The first molten metal is subjected to centrifugal spray pyrolysis, with droplet size of 50 μm and pyrolysis temperature of 800℃, to obtain a metal oxide with particle size D50 = 10.5 μm and chemical formula Ni. 0.65 Co 0.15 Mn 0.20 O 2.4 The particle size is 200~300nm; S2, Preparation of metal hydroxides a. Prepare a 2.0 mol / L second metal solution by mixing nickel chloride, cobalt chloride, and manganese chloride in a molar ratio of nickel, cobalt, and manganese of 65:15:20. b. Add pure water, ammonia water and 32% NaOH to the reaction vessel as the reaction base liquid; c. The second metal liquid, ammonia water, and 32% NaOH were subjected to a co-precipitation reaction at a temperature of 50℃ and a pH of 11.5. d. After the reaction stops, the product is filtered, washed, and dried to obtain a metal hydroxide with the chemical formula Ni. 0.65 Co 0.15 Mn 0.20 (OH)2, particle size D50 = 3.8 μm; S3. The metal oxide and metal hydroxide are crushed to a particle size of 1.0 μm. They are then ground with lithium salt (lithium carbonate) and additive (boric acid) in pure water. The mass ratio of the metal oxide to the total mass of the metal oxide and metal hydroxide is 0.9:1, the molar ratio of lithium to metal is 1.06, and the mass ratio of the additive to the total mass of the metal oxide and metal hydroxide is 0.005:1. After grinding into nanoparticles with D50 = 0.5 μm, they are subjected to spray heat treatment with a droplet size of 60 μm and a heat treatment temperature of 200℃ to obtain a lithium-containing composite precursor, wherein Li:(Ni+Co+Mn) = 1.06 and particle size D50 = 10.8 μm. S4. The lithium-containing composite precursor was sintered at 890℃ in an oxygen atmosphere for 11 hours, and then crushed to obtain a single-crystal lithium-ion battery cathode material. The chemical equation is LiNi. 0.65 Co 0.15 Mn 0.20 O2, particle size D50=4.2μm.
[0030] Comparative Example 1: Includes the following steps: S1. Prepare a 2.0 mol / L second metal solution by mixing nickel chloride, cobalt chloride, and manganese chloride in a molar ratio of nickel, cobalt, and manganese of 65:15:20; dissolve magnesium chloride to obtain a 1.0 mol / L salt solution. S2. Add pure water, complexing agent and precipitant to the reaction vessel as the reaction base liquid; S3. The second metal liquid, magnesium chloride solution, ammonia water, and 32% NaOH are continuously added to the reactor to maintain the temperature inside the reactor at 50℃, the ammonia concentration at 0.1mol / L, and the pH at 11.5, and a co-precipitation reaction is carried out. S4. After the reaction stops, the product is filtered, washed, and dried to obtain a metal hydroxide. The chemical equation is (Ni 0.65 Co 0.15 Mn 0.20 ) 0.99 Mg 0.01 (OH)2, particle size D50 = 3.8 μm; S5. Metal hydroxide, lithium carbonate, and additive (boric acid) are mixed, where Li:(Ni+Co+Mn)=1.04, and the mass ratio of boric acid to metal hydroxide is 0.005:1. After mixing, the mixture is sintered at 950℃ in an oxygen atmosphere for 18 hours, and then crushed to obtain a single-crystal lithium-ion battery cathode material. The chemical equation is Li(Ni) 0.65 Co 0.15 Mn 0.20 ) 0.99 Mg 0.01 O2, with a particle size D50 of 4.2 μm.
[0031] Comparative Example 2: Includes the following steps: S1. Prepare a 2.0 mol / L metal solution by mixing nickel chloride, cobalt chloride, and manganese chloride in a molar ratio of nickel, cobalt, and manganese of 65:15:20. S2. The molten metal is subjected to spray pyrolysis with droplet size of 50 μm and pyrolysis temperature of 800℃ to obtain metal oxide. The chemical equation is Ni. 0.65 Co 0.15 Mn 0.20 O 2.4 Particle size D50 = 10 μm, primary particle size 200~300 nm; S3. After crushing the metal oxide, small metal oxide particles are obtained with D50 = 1.5 μm. S4. Small-particle metal oxide, lithium carbonate, and additive (boric acid) are mixed, with Li:(Ni+Co+Mn)=1.04 and the mass ratio of boric acid to small-particle metal oxide being 0.005:1. The mixture is then sintered at 960℃ in an oxygen atmosphere for 18 hours. After crushing, a single-crystal lithium-ion battery cathode material is obtained. The chemical equation is LiNi. 0.65 Co 0.15 Mn 0.20 O2, with a particle size D50 of 4.2 μm.
[0032] Table 1 Electrical Performance Test Table for Single Crystal Cathode Materials
[0033] As can be seen from Table 1 above, and combined with the electron micrographs of Example 1 and the two comparative examples, Examples 1 and 2 of the present invention have high sintering activity due to the large amount of lithium-containing composite precursors, in which the metal oxides, metal hydroxides, and lithium salts are all nanoparticles. In addition, the metal hydroxides serve as crystal nuclei, resulting in more rounded single crystals after sintering and better electrochemical performance. In contrast, Comparative Example 1 has small-particle hydroxide precursors, and its electrochemical performance after sintering is similar to that of Example 1, but the amount of precursors is small and the sintering time is long. Comparative Example 2 has a broken metal oxide precursor with low activity, resulting in poor electrochemical performance after sintering. At the same time, the amount of precursors is small and the production capacity is low.
[0034] In summary, this invention utilizes low-cost nano-metal oxide particles and hydroxides, along with lithium salts and additives, to form a large-particle, highly active composite precursor through direct spray heat treatment. This method offers advantages such as large packing capacity and low sintering cost. The close contact between the nano-metal particles and the lithium salt significantly shortens the lithium diffusion distance during sintering; simultaneously, the liquid phase environment formed by the melting of the additives further promotes lithium diffusion, thereby shortening the sintering time. Furthermore, due to its layered structure similar to the target cathode material, the metal hydroxide can act as a nucleus to promote the formation of layered single-crystal cathode materials, ultimately resulting in superior electrochemical performance.
[0035] The above embodiments are only for illustrating the technical concept and features of the present invention, and are intended to enable those skilled in the art to understand the content of the present invention and implement it accordingly. They should not be construed as limiting the scope of protection of the present invention. All equivalent changes or modifications made in accordance with the spirit and essence of the present invention should be covered within the scope of protection of the present invention.
Claims
1. A lithium-containing composite precursor, characterized in that: The precursor is a secondary particle formed by the stacking of primary particles. It is composed of metal oxides, metal hydroxides, lithium salts and additives, with a particle size D50 of 5~50μm. The primary particles are nano-sized with a size of less than 500nm. The chemical formula of the metal oxide is (Ni x1 Co y1 Mn z1 Al t1 ) a1 M1 b1 O c1 Where 0 < x1 < 1, 0 < y1 < 1, 0 ≤ z1 < 1, 0 ≤ t1 < 0.1, x1 + y1 + z1 + t1 = 1, 0.9 < a1 ≤ 1, 0 ≤ b1 < 0.1, a1 + b1 = 1, c1 satisfies chemical valence balance, and M1 is one or more of the elements calcium, magnesium, aluminum, titanium, zirconium, tungsten, yttrium, strontium, niobium, molybdenum, vanadium, tantalum, boron, or phosphorus. The chemical formula of the metal hydroxide is (Ni x2 Co y2 Mn z2 Al t2 ) a2 M2 b2 (OH) c2 , 0 < x2 < 1, 0 < y2 < 1, 0 ≤ z2 < 1, 0 ≤ t2 < 0.1, x2 + y2 + z2 + t2 = 1, 0.9 < a2 ≤ 1, 0 ≤ b2 < 0.1, a2 + b2 = 1, c2 satisfies chemical valence balance, M2 is one or more of the elements calcium, magnesium, aluminum, titanium, zirconium, tungsten, yttrium, strontium, niobium, molybdenum, vanadium, tantalum, boron or phosphorus; The lithium salt is one or more of lithium carbonate, lithium bicarbonate, lithium hydroxide, lithium oxide, lithium acetate, lithium nitrate, and lithium oxalate. The additive is one or more of the carbonates, oxides, and hydroxides of element M3, where M3 is one or more of the elements calcium, magnesium, aluminum, titanium, zirconium, tungsten, yttrium, strontium, niobium, molybdenum, vanadium, tantalum, boron, or phosphorus. The mass ratio of the metal oxide to the total mass of the metal oxide and metal hydroxide is 0 to 1:1, and the ratio is neither 0 nor 1.
2. The lithium-containing composite precursor according to claim 1, characterized in that: The molar ratio of lithium to metal is 0.70~1.50:1, and the mass ratio of additives to the total mass of metal oxides and metal hydroxides is 0~0.1:
1.
3. A method for preparing a lithium-containing composite precursor, characterized in that: The method for preparing a lithium-containing composite precursor according to any one of claims 1 to 2 comprises: S1, Preparation of metal oxides A first metal liquid with a metal concentration of 0.5~5.0 mol / L is obtained by dissolving and mixing the first nickel salt, the first cobalt salt, the first manganese salt and / or the first aluminum salt, and the M1 salt. The first molten metal was spray-pyrolyzed to obtain metal oxides; S2, Preparation of metal hydroxides A second metal liquid with a metal concentration of 1.0~2.5 mol / L is obtained by dissolving a mixture comprising a second nickel salt, a second cobalt salt, a second manganese salt, and / or a second aluminum salt. Dissolve M2 salt to obtain M2 salt solution; Pure water, complexing agent, and precipitant are added to the reaction vessel as the reaction base liquid; The second molten metal, complexing agent, precipitant, and M2 salt solution are continuously added to the reactor simultaneously to maintain the temperature, complexing agent concentration, and solution pH within the reactor for co-precipitation reaction. After the reaction stops, the product is filtered, washed, and dried to obtain metal hydroxide; S3. After crushing the metal oxide and the metal hydroxide, add them to pure water along with lithium salt and additives and grind them into nanoparticles with D50 < 1 μm. Then, perform spray heat treatment to obtain the lithium-containing composite precursor.
4. The method for preparing a lithium-containing composite precursor according to claim 3, characterized in that: In S1, the first nickel salt is one or a combination of nickel nitrate, nickel chloride, and nickel acetate; The first cobalt salt is one or a combination of cobalt nitrate, cobalt chloride, and cobalt acetate; The first manganese salt is one or a combination of manganese nitrate, manganese chloride, and manganese acetate; The first aluminum salt is one or a combination of aluminum nitrate, aluminum chloride, and aluminum acetate; The M1 salt is one or more of the following: calcium salt, magnesium salt, titanium salt, zirconium salt, tungsten salt, yttrium salt, strontium salt, niobium salt, molybdenum salt, vanadium salt, tantalum salt, borate, or phosphate.
5. The method for preparing a lithium-containing composite precursor according to claim 3, characterized in that: In S2, the second nickel salt is one or a combination of nickel sulfate, nickel chloride, nickel nitrate, and nickel acetate; The second cobalt salt is one or a combination of cobalt sulfate, cobalt chloride, cobalt nitrate, and cobalt acetate; The second manganese salt is one or a combination of manganese sulfate, manganese chloride, manganese nitrate, and manganese acetate; The second aluminum salt is one or a combination of aluminum sulfate, aluminum chloride, aluminum nitrate, and aluminum acetate; The M2 salt is one or more of the following: calcium salt, magnesium salt, aluminum salt, titanium salt, zirconium salt, borate, tungsten salt, yttrium salt, strontium salt, niobium salt, molybdenum salt, vanadium salt, tantalum salt, borate, or phosphate. The complexing agent is one or more of the following: ammonia, ammonium sulfate, ammonium chloride, ammonium carbonate, ammonium bicarbonate, ammonium nitrate, and ammonium acetate. The precipitant is one or more of sodium hydroxide and potassium hydroxide, or a combination thereof.
6. The method for preparing a lithium-containing composite precursor according to claim 3, characterized in that: In S1, the atomization method of the spray pyrolysis is one of pressure spray, centrifugal spray, or ultrasonic spray, the droplet size is less than 100μm, and the pyrolysis temperature is 600~1200℃; In S2, the reaction temperature is 40~75℃, the complexing agent concentration is 0.2~0.5mol / L, and the pH range is 10.60~12.60; In S3, the atomization method of the spray pyrolysis is one of pressure spray, centrifugal spray, or ultrasonic spray, the droplet size is less than 100μm, and the heat treatment temperature is 150~900℃.
7. A lithium-ion battery cathode material, characterized in that: The lithium-containing composite precursor described in any one of claims 1 to 2 is mixed with a lithium source and calcined at high temperature in an oxygen atmosphere. After crushing, a single-crystal lithium-ion cathode material with the chemical formula Li(Ni) is obtained. x Co y Mn z Al t ) a M b O c Where 0 < x < 1, 0 < y < 1, 0 ≤ z < 1, 0 ≤ t < 0.1, x + y + z + t = 1, 0.9 < a ≤ 1, 0 ≤ b < 0.1, a + b = 1, c satisfies chemical valence balance, M is one or more of the elements calcium, magnesium, aluminum, titanium, zirconium, tungsten, yttrium, strontium, niobium, molybdenum, vanadium, tantalum, boron or phosphorus, and the particle size D50 of the cathode material is 3~5 μm.
8. The lithium-ion battery cathode material according to claim 7, characterized in that: The lithium source is one or a combination of lithium carbonate, lithium bicarbonate, and lithium hydroxide. The calcination temperature is 650℃~1100℃, the oxygen concentration in the oxygen-rich atmosphere is 60%~100%, and the calcination time is 8~16h.
9. A lithium-ion battery, characterized in that: It includes a positive electrode sheet, which is made from a lithium-ion battery positive electrode material as described in claim 8.
Citation Information
Patent Citations
Monocrystal ternary precursor, positive electrode material and preparation method
CN118084080A
Magnesium oxide-doped ternary precursor and preparation method thereof
CN118684274A
Ternary positive electrode material and preparation method thereof
CN118754207A